Hypoxia-induced pulmonary vascular remodeling: contribution of the adventitial fibroblasts - Stenmark, K R; Bouchey, D; Nemenoff, R; Dempsey, E C; Das, M (Physiological research, 2000)
Vascular repair in response to injury or stress (often referred to as remodeling) is a common complication of many cardiovascular abnormalities including pulmonary hypertension, systemic hypertension, atherosclerosis, vein graft remodeling and restenosis following balloon dilatation of the coronary artery. It is not surprising that repair and remodeling occurs frequently in the vasculature in that exposure of blood, vessels to either excessive hemodynamic stress (e.g. hypertension), noxious blood borne agents (e.g. atherogenic lipids), locally released cytokines, or unusual environmental conditions (e.g. hypoxia), requires readily available mechanisms to counteract these adverse stimuli and to preserve structure and function of the vessel wall. The responses, which were presumably evolutionarily developed to repair an injured tissue, often escape self-limiting control and can result, in the case of blood vessels, in lumen narrowing and obstruction to blood flow. Each cell type (i. e. endothelial cells, smooth muscle cells, and fibroblasts) in the vascular wall plays a specific role in the response to injury. However, while the roles of the endothelial cells and smooth muscle cells (SMC) in vascular remodeling have been extensively studied, relatively little attention has been given to the adventitial fibroblasts. Perhaps this is because the fibroblast is a relatively ill-defined cell which, at least compared to the SMC, exhibits few specific cellular markers. Importantly though, it has been well demonstrated that fibroblasts possess the capacity to express several functions such as migration, rapid proliferation, synthesis of connective tissue components, contraction and cytokine production in response to activation or stimulation. The myriad of responses exhibited by the fibroblasts, especially in response to stimulation, suggest that these cells could play a pivotal role in the repair of injury. This fact has been well documented in the setting of wound healing where a hypoxic environment has been demonstrated to be critical in the cellular responses. As such it is not surprising that fibroblasts may play an important role in the vascular response to hypoxia and/or injury. This paper is intended to provide a brief review of the changes that occur in the adventitial fibroblasts in response to vascular stress (especially hypoxia) and the role the activated fibroblasts might play in hypoxia-mediated pulmonary vascular disease.
Keywords: plicní oběh; buněčné dělení; cévy; fibroblasty; Animals; Fibroblasts; Cell Division; lidé; Hypoxia; Cell Death; Pulmonary Circulation; Blood Vessels; Humans; zvířata; buněčná smrt; hypoxie